If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -75 = -12x + 107 Reorder the terms: -75 + 2x = -12x + 107 Reorder the terms: -75 + 2x = 107 + -12x Solving -75 + 2x = 107 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. -75 + 2x + 12x = 107 + -12x + 12x Combine like terms: 2x + 12x = 14x -75 + 14x = 107 + -12x + 12x Combine like terms: -12x + 12x = 0 -75 + 14x = 107 + 0 -75 + 14x = 107 Add '75' to each side of the equation. -75 + 75 + 14x = 107 + 75 Combine like terms: -75 + 75 = 0 0 + 14x = 107 + 75 14x = 107 + 75 Combine like terms: 107 + 75 = 182 14x = 182 Divide each side by '14'. x = 13 Simplifying x = 13
| 0=-2*sin(2x) | | 19/2-[9/2{5/2-9/2-4}] | | (x+0.05)y=1.05y*x | | -41-x=19-5 | | X-7=x+19 | | 3w+3x=99 | | 3k^2-12k+12=75 | | -20+4x=43+x | | 2w+1x=49 | | 3k(k+1)=0 | | 9x-2=6x+13 | | 2x^2-5x-3=-3 | | 2x-5y+5xy=14 | | 2xy-5y+5xy=14 | | 36x-54+49=0 | | 2x^4/6x^2 | | y=32x+2 | | y=22x+1 | | 22=ax+1 | | 16-3x=36-8x | | 2x+7=19-2x | | 5ab+3ba= | | x/=6 | | so/ve | | y=x^3+9x-1 | | 3x+11=-17-4x | | 28p=70 | | 0.16x=1 | | f(x)=x^3-x^2+8x | | 80d=60 | | 8x-20=4x+8 | | Y=(10*7+90) |